Atmospheric Input and Seasonal Inventory of Dissolved Iron in the Sargasso Sea: Implications for Iron Dynamics in Surface Waters of the Subtropical Ocean. Issue 6 (21st March 2023) - Sedwick, P. N.; Sohst, B. M.; Buck, K. N.; Caprara, S.; Johnson, R. J.; Ohnemus, D. C.; Sofen, L. E.; Tagliabue, A.; Twining, B. S.; Williams, T. E.
Abstract: Constraining the role of dust deposition in regulating the concentration of the essential micronutrient iron in surface ocean waters requires knowledge of the flux of seawater‐soluble iron in aerosols and the replacement time of dissolved iron (DFe) in the euphotic zone. Here we estimate these quantities using seasonally resolved DFe data from the Bermuda Atlantic Time‐series Study region and weekly‐scale measurements of iron in aerosols and rain from Bermuda during 2019. In response to seasonal changes in vertical mixing, primary production and dust deposition, surface DFe concentrations vary from ∼0.2 nM in early spring to >1 nM in late summer, with DFe inventories ranging from ∼30 to ∼80 μmol/m 2, respectively, over the upper 200 m. Assuming the upper ocean approximates steady state for DFe on an annual basis, our aerosol and rainwater data require a mean euphotic‐zone residence time of ∼0.8–1.9 years for DFe with respect to aeolian input. Plain Language Summary: Primary production by phytoplankton in ocean surface waters is the foundation of the marine ecosystem, and plays a key role in maintaining the ocean‐atmosphere balance of carbon dioxide, which regulates global climate. Iron is an essential micronutrient that is required by phytoplankton, and the availability of dissolved iron (DFe) is thought to limit phytoplankton growth over large areas of the ocean. In this context, it is important to constrain the sources and persistence of DFe in surface ocean waters, which control the amount of DFe that is available to support phytoplankton growth. This study focuses on the Bermuda region of the North Atlantic Ocean, where deposition of airborne soil dust is the major source of DFe to surface waters. By combining measurements of the atmospheric loading and solubility of iron in soil dust over Bermuda with measurements of DFe in adjacent ocean waters over a full year, we are able to estimate the rate of supply of DFe from dust deposition in this region, as well as the average time that this DFe persists in the surface ocean. The latter, termed the DFe replacement time, is around 1 year, which agrees well with recent estimates from comparable ocean regions. Key Points: An imbalance between input and removal produces an ∼3‐fold seasonal increase in the euphotic‐zone inventory of dissolved iron (DFe) near Bermuda Analyses of iron in seasonal‐scale aerosol, rain and water‐column samples allow direct estimates of the replacement time of DFe We derive a mean residence time of ∼0.8–1.9 years for DFe in the euphotic zone (<200 m) of the Sargasso Sea near Bermuda